Effects of bacteriocin-producing Lactiplantibacillus plantarum on bacterial community and fermentation profile of whole-plant corn silage and its in vitro ruminal fermentation, microbiota, and CH4 emissions - Ziqian Li; Usman, S.; Jiayao Zhang; Yixin Zhang; Su, R.; Hu Chen; Qiang Li; Mengya Jia; Amole, Tunde A.; Xusheng Guo (Springer, 2024)
Background Silage is widely used to formulate dairy cattle rations, and the utilization of antibiotics and methane emissions are 2 major problems for a sustainable and environmentally beneficial ruminant production systems. Bacteriocin has received considerable attention because of its potential as an alternative to antibiotics in animal husbandry. However, the impact of bacteriocin-producing lactic acid bacteria on the microbiological conversion process of whole-plant corn silage and rumen fermentation remains limited. The purpose of this study was to assess the effect of 2 class IIa bacteriocin-producing strains Lactiplantibacillus plantarum ATCC14917 and CICC24194 on bacterial community composition and ensiling profiles of whole-plant corn silage and its in vitro rumen fermentation, microbiota, and CH4 emissions.